Powerless in Gaza. - Weinberger, S.
In November of 2008, the backup batteries unexpectedly failed at a power plant in the Gaza Strip. Almost anywhere else, the incident would have been a blip, forgotten a week later. But this is Gaza-blockaded by Israel and Egypt and cut off from the Palestinian National Authority in the West Bank. It's a place where more than a million and a half people inhabit a strip of land not even one-third the size of the city of Los Angeles... and where there is only one power plant.
Keywords: Backup batteries; Power plants; Power system restoration